Did policies to abate atmospheric emissions from traffic have a positive effect in London?. (November 2016) - Font, Anna; Fuller, Gary W.
Abstract: A large number of policy initiatives are being taken at the European level, across the United Kingdom and in London to improve air quality and reduce population exposure to harmful pollutants from traffic emissions. Trends in roadside increments of nitrogen oxides (NOX ), nitrogen dioxide (NO2 ), particulate matter (PM), black carbon (CBLK) and carbon dioxide (CO2 ) were examined at 65 London monitoring sites for two periods of time: 2005–2009 and 2010–2014. Between 2005 and 2009 there was an overall increase in NO2 reflecting the growing evidence of real world emissions from diesel vehicles. Conversely, NO2 decreased by 10%·year −1 from 2010 onwards along with PM2.5 (−28%·year −1 ) and black carbon (−11%·year −1 ). Downwards trends in air pollutants were not fully explained by changes in traffic counts therefore traffic exhaust emission abatement policies were proved to be successful in some locations. PM10 concentrations showed no significant overall change suggesting an increase in coarse particles which offset the decrease in tailpipe emissions; this was especially the case on roads in outer London where an increase in the number of Heavy Good Vehicles (HGVs) was seen. The majority of roads with increasing NOX experienced an increase in buses and coaches. Changes in CO2 from 2010 onwards did not match the downward predictions from reduced traffic flows and improved fleet efficiency. CO2 increased along with increasing HGVs and buses. Polices to manage air pollution provided differential benefits across London's road network. To investigate this, k -means clustering technique was applied to group roads which behaved similarly in terms of trends to evaluate the effectiveness of policies to mitigate traffic emissions. This is the first time that London's roadside monitoring sites have been considered as a population rather than summarized as a mean behaviour only, allowing greater insight into the differential changes in air pollution abatement policies. Graphical abstract: Highlights: Short-term trends in roadside increments of air pollutants along 65 roads in London. Great variability of response to abatement policies across London's roads. General decrease of NOX and NO2 concentrations in 2010–2014. Roads with increased NOX observed more buses and heavy good vehicles. PM2.5 concentrations decreased along with black carbon; PM10 coarse increased. Abstract : Trends in roadside air pollutants in London: results from a large population of monitoring sites.